2002
DOI: 10.1080/15428110208984713
|View full text |Cite
|
Sign up to set email alerts
|

Grip Force and Muscle Activity Differences Due to Glove Type

Abstract: The purpose of this study was to investigate the effects of different types and sizes of gloves on external grip force and muscle activity. Twenty-one male and seven female volunteers served as subjects. Each subject performed two maximum voluntary grip contractions while wearing each of the 10 glove types. Results indicated significant differences in the effects of different glove types on the peak force, ratio of peak force to normalized flexor muscle EMG activity, and the ratio of peak force to coactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 9 publications
6
35
0
4
Order By: Relevance
“…Previous studies have found that wearing gloves decreases the maximum grip force that can be exerted when compared with the bare hand (Mital et al, 1994;Tsaousidis and Freivalds, 1997;Kovacs et al, 2002;Willms, 2006). A 15e30 per cent decrease in grip force transferred to an implement was illustrated when wearing gloves (Tsaousidis and Freivalds, 1997).…”
Section: Reviewmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous studies have found that wearing gloves decreases the maximum grip force that can be exerted when compared with the bare hand (Mital et al, 1994;Tsaousidis and Freivalds, 1997;Kovacs et al, 2002;Willms, 2006). A 15e30 per cent decrease in grip force transferred to an implement was illustrated when wearing gloves (Tsaousidis and Freivalds, 1997).…”
Section: Reviewmentioning
confidence: 93%
“…In addition, manual work requiring high hand forces will promote fatigue and risk of developing MSD (Armstrong et al, 1987;Keyserling et al, 1993;Rock et al, 2001;Kovacs et al, 2002). Many characteristics of gloves could decrease performance, increase loading and enhance the risk of MSD development.…”
Section: Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…EMG measures would also identify which muscles are most affected. Four studies have used EMG measures to assess gloves (Fleming et al, 1997;Kovacs et al, 2002;Mital et al, 1994;Sudhakar et al, 1988). The three studies that evaluated the level of forearm muscle activation used tasks requiring the production of MVCs (Kovacs et al, 2002;Mital et al, 1994;Sudhakar et al, 1988).…”
Section: Introductionmentioning
confidence: 99%